XMM-Newton observation of SNR J0533-7202 in the Large Magellanic Cloud - Kavanagh, P. J.; Sasaki, Manami; Whelan, E. T.; Maggi, P.; Haberl, Frank; Bozzetto, L. M.; Filipovic, M. D.; Crawford, E. J. (Astronomy & Astrophysics, 2015)
Aims: We present an X-ray study of the supernova remnant SNR J0533-7202 in the Large Magellanic Cloud (LMC) and determine its physical characteristics based on its X-ray emission. Methods: We observed SNR J0533-7202 with XMM-Newton (background flare-filtered exposure times of 18 ks EPIC-pn and 31 ks EPIC-MOS1, EPIC-MOS2). We produced X-ray images of the supernova remnant, performed an X-ray spectral analysis, and compared the results to multi-wavelength studies. Results: The distribution of X-ray emission is highly non-uniform, with the south-west region much brighter than the north-east. The detected X-ray emission is correlated with the radio emission from the remnant. We determine that this morphology is most likely due to the supernova remnant expanding into a non-uniform ambient medium and not an absorption effect. We estimate the remnant size to be 53.9 (±3.4) × 43.6 (±3.4) pc, with the major axis rotated 64° east of north. We find no spectral signatures of ejecta emission and infer that the X-ray plasma is dominated by swept up interstellar medium. Using the spectral fit results and the Sedov self-similar solution, we estimate the age of SNR J0533-7202 to be 17-27 kyr, with an initial explosion energy of (0.09-0.83) × 1051 erg. We detected an X-ray source located near the centre of the remnant, namely XMMU J053348.2-720233. The source type could not be conclusively determined due to the lack of a multi-wavelength counterpart and low X-ray counts. We found that it is likely either a background active galactic nucleus or a low-mass X-ray binary in the LMC. Conclusions: We detected bright thermal X-ray emission from SNR J0533-7202 and determined that the remnant is in the Sedov phase of its evolution. The lack of ejecta emission prohibits us from typing the remnant with the X-ray data. Therefore, the likely Type Ia classification based on the local stellar population and star formation history reported in the literature cannot be improved upon.
Keywords: ISM: supernova remnants; Magellanic Clouds; X-rays: ISM